Costa Rica : Social Spending and the Poor, Volume 2. Social Sector Performance in the 90's - Facing the Challenges - World Bank (Washington, DC, 2013)
The report reviews the substantial progress Costa Rica made over the past decade in reducing poverty and improving social indicators. However, while economic growth certainly reduced poverty rates, the country's recent experience shows that relying on economic growth and increased public spending alone will not necessarily yield sufficient reductions in poverty. Moreover, the rising concern that fiscal pressure will limit possibilities of increasing social spending suggests further efficiency in the sector. Even though coverage of education and health remains almost universal in basic education, and so is access to healthcare services, worrying signs in social sector indicators suggest a decline in the efficiency of social spending. The report addresses three key issues, namely, a) Who are the poor and vulnerable groups in Costa Rica? b) What has been the impact of social spending on programs that aim to improve the welfare of the poor? and c) Which are the improvements required, and how can government spending be used more effectively to reach the poor and reduce poverty? In response to these questions, the report presents an in-depth, multi-dimensional analysis of poverty, examines the effectiveness of government policies, and social sector spending on the poor, and, uses the empirical findings to identify options and priorities for improving social sector spending and reducing poverty in the future. Recommendations emphasize improving the institutional framework, coordinating the implementation of social programs, as well as increasing flexibility in programs so as to be more responsive to the needs of the poor.